Dune belt restoration effectiveness assessed by UAV topographic surveys (northern Adriatic coast, Italy) - R. A. Faelga; L. Cantelli; S. Silvestri; B. M. S. Giambastiani (Biogeosciences, 2023)
Unoccupied aerial vehicle (UAV) monitoring surveys are used to assess a dune restoration project in the protected natural area of the Bevano River mouth on the northern Adriatic coast (Ravenna, Italy). The impacts of the installed fences to aid dune development are quantified in terms of sand volume and vegetation cover changes over 5 years using a systematic data processing workflow based on structure-from-motion (SfM) photogrammetry and the Geomorphic Change Detection (GCD) toolset applied to two drone surveys in 2016 and 2021. Accuracy assessment is performed using statistical analysis between ground-truth and model elevation data. Results show that the fence proves to be effective in promoting recovery and growth since significant sand deposition was observed along the dune foot and front – a total area of 3799 m2, volume of 1109 m3, and average depositional depth of 0.29 m. Progradation of around 3–5 m of the foredune and embryo development were also evident. There was a decrease in blowout features of about 155 m2 due to increased deposition and vegetation colonization. There was also an average percent increase of 160 % on wave-induced driftwood and/or debris along the beach and of 9.6 % vegetation within the fence based on the cover analysis on selected transects. Erosion of around 1439 m2 is apparent mostly at the northern portion of the structure, which could be accounted for by the aerodynamic and morphodynamic conditions around the fence and its configuration to trap sediments and efficiency in doing so. Overall, dune fencing coupled with limiting debris cleaning along the protected coast was effective. The proposed workflow can aid in creating transferable guidelines to stakeholders in integrated coastal zone management (ICZM) implementation on Mediterranean low-lying sandy coasts.